2016
DOI: 10.1038/srep34332
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA let-7f-5p Inhibits Porcine Reproductive and Respiratory Syndrome Virus by Targeting MYH9

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most important viral pathogens in the swine industry. Current antiviral strategies do not effectively prevent and control PRRSV. Recent reports show that microRNAs (miRNAs) play vital roles in viral infections by post transcriptionally regulating the expression of viral or host genes. Our previous research showed that non-muscle myosin heavy chain 9 (MYH9) is an essential factor for PRRSV infection. Using bioinformatic prediction and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
(49 reference statements)
2
20
0
Order By: Relevance
“…Similar to the results of this study, our previous study found that miR-10a-5p could suppress PRRSV replication by inhibiting host SRP14 expression [25]. miRNA let-7f-5p significantly inhibits PRRSV replication by inhibiting MYH9 expression [26]. These miRNAs can modulate host factors in response to antiviral responses of the body after PRRSV infection.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to the results of this study, our previous study found that miR-10a-5p could suppress PRRSV replication by inhibiting host SRP14 expression [25]. miRNA let-7f-5p significantly inhibits PRRSV replication by inhibiting MYH9 expression [26]. These miRNAs can modulate host factors in response to antiviral responses of the body after PRRSV infection.…”
Section: Discussionsupporting
confidence: 88%
“…Quantitative PCR (qPCR) was performed using the Step One Plus Real-Time PCR System (Applied Biosystems) and FastStart Universal SYBR Green Master Mix (Roche) with RXRB-specific forward and reverse primers (5′-GTGA AGCC ACCA GTCT TAGGG-3′ and 5′-AGTA GGTC AGGT CCTT ACGGATG-3, respectively) and PRRSV ORF7-specific forward and reverse primers (5′-AGATCATCGCCCAACAAAAC-3′ and 5′-GACACAATTGCCGCTCACTA-3′, respectively) being used as described previously [37]. HPRT1 mRNA was used as an internal standard for quantification, and HPRT1specific forward and reverse primers (5′-TGGA AAGA ATGT CTTG ATTG TTGAAG-3′ and 5′-ATCT TTGG ATTA TGCT GCTTGACC-3′, respectively) were used for detection [26].…”
Section: Quantitative Reverse Transcription-pcr (Rt-qpcr)mentioning
confidence: 99%
“…HP-PRRSV nsp4 has greater inhibitory effect on IFNβ than nsp4 of less pathogenic strains. As discussed above, nsp1α binds to and degrades SLA-I (Du et al, 2016a), A recent study supports this finding that HP-PRRSV nsp4 also downregulates the cellular level of β2microglobulin (β2M) (Qi et al, 2017), which forms a heterotrimeric complex with the SLA-I heavy chain and plays a critica1 role in SLA-I antigen presentation. PRRSV nsp4 binds to the B2M promoter and suppresses β2M transcription.…”
Section: Suppression Of Type I Interferon Responsementioning
confidence: 64%
“…Interestingly, nsp1α binds to swine leukocyte antigen class I (SLA-I) and mediates the SLA-I degradation in a ubiquitin-proteasome-dependent manner (Du et al, 2016a). It is thus tempting to speculate that nsp1α may have an ubiquitin E3 ligase activity.…”
Section: Suppression Of Type I Interferon Responsementioning
confidence: 99%
See 1 more Smart Citation